Subpicosecond dynamics in DNA from leaves of in vitro-grown apple plants: A SERS study. Issue 1 (2011) - Muntean Muntean, Cristina M. Cristina M.; Bratu Bratu, Ioan Ioan; Leopold Leopold, Nicolae Nicolae; Purcaru Purcaru, Monica A. P. Monica A. P.
Abstract : In this work the SERS total half bandwidths of five genomic DNAs from in vitro -grown apple leaf tissues ( Malus domestica Borkh., Fam Rosaceae, cvs. Florina, Rebra, Goldrush, Romus 3 and Romus 4) have been measured. We have shown that surface-enhanced Raman scattering can be used to study the fast subpicosecond dynamics of DNA in the proximity of a metallic surface. The dependencies of the total half bandwidths and of the global relaxation times, on DNA molecular subgroup structure, on the type of genomic apple plant DNA and on time, are reported. An example of the time-dependence of SERS band parameters of DNA, in the proximity of silver nanoparticles, has been given. It is shown that changes in the subpicosecond surface dynamics of molecular subgroups in genomic DNAs from in vitro -grown apple leaf tissues can be monitored with surface-enhanced Raman spectroscopy. Particularly, the SERS band parameters for the vibrations near 757 cm –1 (dT), 773 cm –1 (dC), 929 cm –1 (deoxyribose), 1087 cm –1 (PO2 – symmetric stretch, backbone), 1127 cm –1 (dA), 1181 cm –1 (ring vibrations of dG, dT, dC), 1311 cm –1 (dA), 1362 cm –1 (dT, dA), 1510 cm –1 (dA), 1573 cm –1 (dG, dA) and 1650 cm –1 [dT(C═O), δ(H2 O)] of genomic DNAs from apple leaves are presented. In our study, the full widths at half-maximum (FWHM) of the bands in genomic DNAs from in vitro -grown apple leaf tissues are typically in the wavenumber range from 14 to 52 cm –1 . Besides, it can be observed that molecular relaxation processes studied in this work, have a global relaxation time smaller than 0.76 ps and larger than 0.20 ps. A comparison between different ranges of FT-Raman and SERS band parameters of DNA extracted from leaf tissues, respectively, is given. We have found that the bands of DNA from Romus 3 and Rebra cultivars are suitable for studying the dynamical behaviour of molecular subgroups, in genomic nucleic acids extracted from in vitro -grown apple plants.